Professional iOS network programming: connecting the enterprise to the iPhone® and iPad - Cox, Jack; Jones, Nathan; Szumski, John (WILEY, 2012)
Learn to develop iPhone and iPad applications for networked enterprise environments The iPhone and iPad have made a powerful impact on the business world. Developers creating iOS apps for the enterprise face unique challenges involving networking, system integration, security, and device management. This Wrox guide provides everything you need to know to write iOS apps that integrate with enterprise network resources, providing options for networking iOS devices to enterprise systems and to each other. -Offers a complete compendium of methods and techniques for networked communication between iOS applications and other platforms and devices -Includes instruction on incorporating synchronous and asynchronous HTTP requests, security, communication issues, and more -Covers payload handling, network security, GameKit and Bonjour communications, and low-level network communications Professional iOS Network Programming focuses on the networking aspects of iOS and its relationship to remote data sources, offering a truly unique approach.